Institutional Arrangement of the Regional People’s Representative Council in State Administration System of Republic of Indonesia - Lukman Hakim (NOTARIIL Jurnal Kenotariatan, 2020)
Due to repeated changes in the operational arrangements, there is a lack of clarity about the essence of these institutions, which in turn affects their position, duties, functions, and institutional roles. This study aims to find the essence of the Regional People’s Representative Council institutions in accordance with the constitutional system in the Republic of Indonesia. This study was designed in normative juridical research namely identifying, classifying, and analyzing legal materials based on the norms and principles of constitutional law. The results show that there is still no normative agreement about the Regional People’s Representative Council, either institutionally as a regional legislative institution or as an element of regional government. These two methods resulted in different legal consequences. For this reason, it is necessary to redefine the Regional People’s Representative Council. The research shows that institutional arrangements for the council needs to be carried out through stages: constitutional structuring; arrangement/synchronization of laws and regulations (position structure) of the council with regional government laws, electoral regulations, and arrangements in relation to the council with government institutions in the region. The conclusion is that within the framework of an ideal constitutional system, it is necessary to clarify the essence of the Regional People’s Representative Council to ensure legal certainty. Clarity for the institution would greatly influence its authority, duties, and institutional functions. For this reason, institutional arrangements for the council need to proceed in stages to achieve clarity about the relevant questions.